TINGKAT KECUKUPAN ZAT GIZI MAKRO DAN STATUS GIZI PASIEN TUBERKULOSIS DENGAN SPUTUM BTA (+) DAN SPUTUM BTA (–) - Rina Wasesa Aprilia Lazulfa; Bambang Wirjatmadi; Merryana Adriani (Media Gizi Indonesia, 2016)
Tuberculosis is an infectious disease caused by mycobacterium t uberculosis germs. Germs in form of droplets spread through saliva splashes out when coughing, sneezing and talking then inhaled during breathing. The degree of sputum smear positivity of patients describe the increasing number of  tuberculosis bacteria in the lungs that could potentially transmit the infection. In general, patients with  tuberculosis have decreased appetite which impact on weight loss. This research was comparative observational analytic research using cross sectional approach with simple random sampling conducted at the Hospital Asy-Syaaﬁ  Pamekasan with a sample size of 50 people. The results of Mann Whitney test showed a signiﬁ cant difference in  adequacy level of energy (p= 0.026), carbohydrates (p = 0.000),  protein (p = 0.001), fat (p = 0.029) and nutritional status (p = 0.022) between the groups of  tuberculosis with sputum smear (+) and sputum smear (-). It was concluded that adequacy level (energy, p rotein, fat and carbohydrates) and nutrition status among respondents t uberculosis sputum smear (+) have signiﬁ cant differences with the respondent t uberculosis sputum smear (-).